To remove or not to remove: Intraconal metallic foreign body following perforating ocular injury - Kumudini Subedi; Sangita Pradhan; Raghunandan Byanju (Journal of Karnali Academy of Health Sciences)
Background: Foreign bodies (FB) are implicated in 17-30% of penetrating ocular injuries. We encountered 2 cases of perforating ocular trauma with metallic intra-orbital FB in 2 teenage males.